Caracterización clínica y terapéutica de la Espondilitis Anquilosante. - Caguano Cudco, Edilvanny Marisol (2024)
Ankylosing spondylitis (AS) is a chronic inflammatory pathology; its development depends on the predisposition, age, sex and family history of each patient. Among the options for its control are pharmacological, non-pharmacological and biological treatments, together with physical activities. The most commonly used pharmacological drugs are non-steroidal anti-inflammatory drugs (NSAIDs) and disease modulating treatments (DMARDs). Because of the possible variables that may occur within the treatments, their follow-up is essential. The objective of this research consisted of conducting an exhaustive review of the literature using specialized databases, such as PubMed, Scielo, ScienceDirect and Readalyc, in order to explore the clinical symptoms and signs and the therapeutic interventions used to treat this disease. Once the search was generated, a total of 217 articles were screened, of which 10 were included for análisis according to exclusion and inclusion criteria. The main diagnostic marker identified was the human leukocyte antigen HLA-B27. The most common clinical presentations include inflammation, low back pain, osteoporosis and arthritis in addition to extra musculoskeletal manifestations such as ocular inflammation (uveitis), chronic inflammatory skin disease (psoriasis) and chronic intestinal inflammation. In addition, the follow-up and monitoring of patients, in order to develop retrospective and observational analyses that serve as a basis for generating appropriate diagnostic guidelines and goals to be met with each patient suffering from the disease.